Vindolanda, UK/Frankfurt, Germany. Eric Birley and the RGK. Roman Frontier Research Networks between Britain and Germany, 1929–1959. Research Conducted September to December 2023 - Teitz, Catherine (e-Forschungsberichte des DAI, 2024)
Eric Birley was a notable British scholar of Roman frontier studies in the middle of the 20th century. Birley worked closely with German scholars, particularly at the Römisch- Germanische Kommission (RGK), before Second World War and resumed collaboration shortly after. Using archives at the Vindolanda Trust and the RGK, this project has traced Birley’s academic networks and his relationship to Germany to study his influence on the growth of Roman frontier studies as a sub-discipline after the war.